Characterization of chronic relapsing antibody mediated arthritis in mice with a mutation in Ncf1 causing reduced oxidative burst - Peibin Liang; Yanpeng Li; Rui Xu; Kutty Selva Nandakumar; Roma Stawikowska; Gregg B. Fields; Rikard Holmdahl (Molecular Biomedicine, 2022)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune disorder affecting joints with a hallmark of autoantibody production. Mannan-enhanced collagen type II (COL2) antibody induced arthritis (mCAIA) in neutrophil cytosolic factor 1(Ncf1) mutation mouse is a chronic disease model imitating RA in mice. In this study, we characterize the chronic phase of mCAIA in Ncf1 mutated (BQ.Ncf1 m1j/m1j) mice. Arthritis was induced by an intravenous injection of anti-COL2 monoclonal antibodies on day 0 followed by intra-peritoneal injections of mannan (from Saccharomyces cerevisiae) on days 3 and 65 in BQ.Ncf1 m1j/m1j and BQ mice. Bone erosion was analysed by computed tomography (CT) and blood cell phenotypes by flow cytometry. Cytokines and anti-COL2 antibodies were analyzed with multiplex bead-based assays. The arthritis in the Ncf1 m1j/m1j mice developed with a chronic and relapsing disease course, which was followed for 200 days and bone erosions of articular joints were evaluated. An increased number of circulating CD11b+ Ly6G+ neutrophils were observed during the chronic phase, together with a higher level of G-CSF (granulocyte colony-stimulating factor) and TNF-α. In conclusion, the chronic relapsing arthritis of mCAIA in the Ncf1 m1j/m1j mice develop bone erosions associated with a sustained neutrophil type of inflammatory responses.